The Association between rs4541843 Polymorphism in miR-182 and Diabetes Mellitus - Arezu Abdi; Maryam Peymani (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Diabetes Mellitus is one of the most common endocrine diseases. The prevalence of type 2 diabetes is higher than other types, accounting for 85-90% of all diabetic cases. The current research aimed at investigating the association between rs4541843 in miR-182 and type 2 diabetes. Materials and methods: In this case-control study, healthy individuals (n=196) and type 2 diabetic patients (n=199) were randomly selected from a target population in Isfahan, Iran. The genotypes for the polymorphism were determined by PCR-RFLP method and the results were confirmed by sequencing. Then, the frequency of the genotypes and alleles were analyzed to determine the association between rs4541843 in miR-182 and the risk of type 2 diabetes, sex, and age at disease onset. Results: The study showed no significant difference between different genotypes in healthy individuals and diabetic patients (P<0.05). Also, no significant association was found between different genotypes of this polymorphism and risk of diabetes considering GG genotype as the reference genotype (P< 0.05). Conclusion: Due to the lack of association between the rs4541843 in miR-182 and risk of diabetes in this population, this polymorphism cannot be used to screen diabetic patients in the target population. Further studies are needed to evaluate the importance of this polymorphism in different populations.